The Arts and Individual and Collective Agency: A Brazilian Favela Case Study - Moayerian, Neda; Poets, Desirée; Stephenson, Max; g, Cathy (Journal of Ethnic and Cultural Studies, 2023)
Brazil’s favela residents have long challenged the dominant media and social narrative that has, for decades, described them via discourses of criminality. This article examines the work of Redes da Maré, a civil society organization that offers cultural spaces and services for community-based creation and diffusion of the arts in its namesake favela. We employ the concepts of the social imaginary as well as individual and collective agency to investigate whether and in what ways a service-providing civil society organization that has adopted a cultural development approach encourages participants’ democratic attitudes and behaviors at the organizational and community level to challenge existing systemic social oppression by fostering participation in the development process and offering a platform for the expression of the voices of those it engages. Our analysis is based in part on interviews with 4 lead organizers and participants in Redes’ Free Dance School of Maré. Our analysis contributes to a more nuanced understanding of the roles the arts can play in encouraging democratic agency and possibility among favela citizens despite adverse political and social conditions exacerbated by neoliberal beliefs and policies.